The Role of Teachers in Guidance and Counseling to Overcome Aggressive Behavior Tendencies of Students in Elementary Schools - Siti Fitria Ningsih; Angga Winata; Khasbi Ainun Najib (Kawakib: Journal of Multidisciplinary Research, 2025)
This study aims to determine the role of teachers in guidance and counseling. The role of teachers in implementing guidance and counseling must be able to involve parties in the school such as students, subject teachers, principals and parents so that the guidance and counseling program can be implemented properly. Because many things or problems often arise in students when following the learning process at school. The role of teachers referred to in this study is the role of teachers as guides, counselors, informants, facilitators, mediators, collaborators, organizers, motivators, directors, initiators, transmitters, and evaluators in achieving educational success in schools. This type of research uses a literature review method. Literature review is a type of research that focuses on the study and analysis of literature, both books, articles, journals, research reports, and other relevant sources of information. The results of this study can be concluded that the role of teachers in guidance and counseling is very important to support the learning process, including helping students adjust and develop according to their needs, talents, interests, and personalities at school.